Case Report: Diffuse Cerebral Microbleeds in Cerebral Autosomal Recessive Arteriopathy With Subcortical Infarcts and Leukoencephalopathy - Wen, Lan; Yuan, Jichao; Li, Shuang; Zhao, Jieyi; Li, Congjun; Li, Jiafei; Han, Yuanyuan; Wang, Chaohua; Li, Guangjian (Frontiers in Neurology, 2022)
Cerebral autosomal recessive arteriopathy with subcortical infarcts and leukoencephalopathy (CARASIL) is a hereditary cerebral small vascular disease caused by a homozygous mutation in the high-temperature requirement A serine peptidase 1 (HTRA1) gene. Cerebral microbleeds (CMBs) are increasingly recognized neuroimaging findings, occurring with cerebrovascular disease and related to different etiology. Mild to moderate CMBs are not unusual in CARASIL, and they are observed to affect cortical and subcortical structures, while a massive CMB, especially in the cerebellum, is rare. In this case, we report a novel mutation of HTRA1 in a 43-year-old woman whose imaging indicated multiple CMBs in all lobes and the brain stem and cerebellum that mimicked cerebral amyloid angiopathy. The amount and location of CMBs vary in CARASIL, and the potential cause is not fully understood. Based on current studies, our patient’s specific imaging findings may be related to a new genetic mutation.